Huertos, diversidad y alimentación en una zona de transición ecológica del estado de México - José Isabel Juan Pérez; Delfino Madrigal Uribe (Ciencia Ergo Sum)
The study of the home gardens in Mexico is important. It represents an alternative food supplement of the families in rural and urban zones. In the zone ecological transitional State of Mexico the diversity of vegetal species in the home gardens is wide, due to the interaction of geographic, climatic, soil, environmental and ecological conditions. The products obtained have diverse uses: nutritional, social, ritual and commercial, being the most important that for subsistence and the social relations